Variability of a predator-prey interaction in the plankton: Encounters and feeding rates of the chaetognath Flaccisagitta enflata upon copepods - Laura Sanvicente-Añorve; Elia Lemus-Santana; Gerardo Molina-Sandoval; Juan J. Cruz-Motta; Marco Violante-Huerta; Margarita Hermoso-Salazar (PLoS ONE, 2026)
This study examined the predator-prey interaction between Flaccisagitta enflata , a dominant chaetognath species, and copepods in the southwestern Gulf of Mexico to investigate the roles of environmental variables and predator-prey encounters in the feeding rate of F. enflata on copepods and to analyze the gut content of the predator throughout three seasons. Zooplankton samples were collected in summer, fall, and winter in both neritic and oceanic waters. Predator-prey encounters were examined under calm and turbulent conditions to test the influence of wind-induced turbulence. Results indicated that encounters varied across seasons and zones: under calm conditions, they ranged from 11 to 75 copepods/chaetognath.day; under turbulent conditions, encounters increased by 1.5 to 1.8 times at the surface. Statistical tests revealed significant differences in feeding rates across seasons and zones: in summer and fall, feeding rates were higher in neritic waters, whereas in winter, they were higher in the oceanic zone. The primary factors influencing feeding rates were temperature, encounter rates, and salinity. Higher summer and fall temperatures resulted in shorter digestion times and, consequently, higher feeding rates (0.44 to 0.74 copepods/chaetognath day). The encounter rates, strongly correlated with copepod density, positively influenced feeding rates, particularly in summer and fall, with the highest values in the neritic zone. The lowest salinity records, caused by river discharges and observed in winter in shelf waters, corresponded with the lowest feeding rates (0.30 copepods/chaetognath.day). Freshwater inflows carrying suspended sediments increase turbidity, which potentially interferes with the predatory mechanisms of F. enflata and diminishes its feeding rates. Specifically, the main ingested copepods were members of the genera Temora and Euaugaptilus. These findings improve our understanding of the predator-prey interaction between the most abundant zooplankton organisms.